HIV/AIDS stigma-associated attitudes in a rural Ethiopian community: characteristics, correlation with HIV knowledge and other factors, and implications for community intervention - Lifson Alan R; Demissie Workneh; Tadesse Alemayehu; Ketema Kassu; May Randy; Yakob Bereket; Metekia Meka; Slater Lucy; Shenie Tibebe (BMC, 2012)
Abstract Background Whether scale-up of HIV prevention and care will reduce negative attitudes and discriminatory practices towards persons living with HIV/AIDS (PLWH) is uncertain. An HIV knowledge and attitude survey was conducted in a rural Ethiopian community where HIV prevention and treatment was being rapidly scaled up. Data were analyzed to identify prevalence of and factors associated with stigma-associated attitudes towards PLWH. Methods We surveyed 561 adults from 250 randomly selected households in the rural town of Arba Minch and surrounding villages about positive or negative attitudes towards PLWH, as well as demographic characteristics, and knowledge about HIV transmission and treatment. Results Eighty percent of respondents agreed with ≥ 1 negative statements indicating blame or shame towards PLWH and 41% agreed with ≥ 1 negative statements associated with distancing themselves from PLWH. However, only 14% expressed negative responses about whether PLWH should receive support from their communities. In multivariate analysis, a greater number of negative attitudes towards PLWH was significantly (p < 0.05) associated with: female gender (Odds Ratio [OR] = 1.51), living in a rural village (vs. town neighborhood) (OR = 3.44), not knowing PLWH can appear healthy (OR = 1.78), lack of knowledge about perinatal transmission (OR = 1.49), lack of knowledge about how HIV is not transmitted (e.g. casual contact) (OR = 2.05), lack of knowledge about HIV treatment (OR = 1.80), and not personally knowing a PLWH (OR = 1.41). Conclusions In a rural Ethiopian setting in which rapid scale-up of HIV treatment occurred, many respondents still characterized HIV as associated with shame or blame, or indicated PLWH would be isolated or discriminated against. HIV stigma can hamper both prevention and treatment programs. We identified multiple issues which, if addressed, can help promote a more positive cycle in which PLWH are appreciated as members of one's own community who are affirmatively interacted with and supported. Stigma reduction programs should address knowledge gaps such as fears of casual contact contagion, and lack of awareness of medical interventions to help prevent HIV disease, as well as building upon community-based attitudes of the importance of supporting and showing compassion for PLWH.